ROLE OF THE EUROPEAN COURT OF HUMAN RIGHTS IN ENSURING OF RIGHTS PROTECTION OF THE CITIZENS OF UKRAINE - Tolkachova, Iryna A.; Pushchyk, Iryna M. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
Purpose: task of the scientific article is research of role of the European Court of Human Rights concerning human rights protection in Ukraine. Methods of research: when writing the article there were used general-theoretical and specially scientific methods of cognition in considering complaints to the European Court of Human Rights. System and structural method made it possible to research international and legal mechanism of access to the European Court of Human Rights as an integral system and highlight elements of its structure. Dogmatic method was used when formulating of conclusions and recommendations of practical nature within the subject matter of research. During writing of the article there were also used Aristotelian methods and modes: analysis, synthesis, induction, deduction, abstracting, modelling etc. Results: it is pointed out that the more effective and qualitative legal protection on domestic level is, the less applications to international and European juridical instances, including the European Court of Human Rights, will be. It is defined that the European Court of Human Rights should be an impetus to changes in the society and reforming of the judicial system of our state, since its role in ensuring of protection of human rights in Ukraine is considerable. Discussion: national legislation, international treaties, which concern activity of the European Court of Human Rights and its judgements.